KAJIAN LITERATUR: HUBUNGAN PEMBELAJARAN ANATOMI KLINIS TERINTEGRASI BEDAH DENGAN KOMPETENSI OPERATIF MAHASISWA KEDOKTERAN - Nadia Purnama Dewi,; Yuliza Birman,; Ade Teti Vani, (Nusantara Hasana Journal, 2025)
To improve students' operative skills, clinical anatomy instruction is crucial in medical education. An approach that integrates anatomy and surgical practice is considered more effective than the conventional method that separates the two. Previous research findings may not be entirely consistent. This study employed a Systematic Literature Review (SLR) with thematic analysis, encompassing quantitative and qualitative studies from the last five years from reputable databases. The selected articles addressed clinical anatomy in a surgical context and its impact on the operative skills of medical students. When clinical anatomy is integrated into surgical education, patients' understanding of applicable anatomy and basic technical skills, including procedures such as cricothyroidotomy, appendectomy, and dissection, improves. Simulation, surgical procedures using experimental animals, and virtual reality technology are all methods that can facilitate learning. These techniques enhance anatomical accuracy, dissection skills, and clinical decision-making based on body structures. The quality of the facilitator, continuity of education, and practice tools (including wet labs and VR/AR) are all factors that influence effectiveness. Challenges include limited time, limited instructional resources, and variations in approaches across institutions. The integration of clinical anatomy into surgical education is recommended to bridge the gap between theory and clinical skills, with a systematic curriculum grounded in real- world practice and simulation.